Foucault's Point of Heresy: 'Quasi-Transcendentals' and the Transdisciplinary Function of the Episteme. (September 2015) - Balibar, Étienne
Major difficulties for readers of Foucault's The Order of Things concern the historical function and the logical construction of the episteme . Our proposal is to link it with another notion, the 'point of heresy', less frequently addressed. This leads to asserting that irreconcilable dilemmas are in fact determined by the type of rationality governing the emergence of common objects of knowledge. It also introduces a possibility of 'walking on two roads': a dialogical adventure within rationality. Foucault is not content with either accepting or rejecting the 'transcendental' question 'What is Man?': with the help of quasi-transcendental categories performing a 'transdisciplinary' function, he wants to reach the 'heretical' point where anthropology becomes historicity within the horizon of finitude.